The Existence of Tuwu Dance in Nias Society - Yeni Cecilia Fa'omasi Hulu; Hernando Laoli; Erwin Anugerah Zebua; Riki Mega Pratama Ndruru; Perdinal Edo Perwira Simbolon; Mauly Purba (Mahesa Research Center (PT. Mahesa Global Publishing), 2024)
The Tuwu Dance is an integral part of the cultural heritage of the Nias people in Indonesia, reflecting their identity and deeply rooted traditions. This research explores key aspects of this traditional dance, including its history, cultural significance, specific movements, and the role it plays in the social fabric of Nias society. The research employs a qualitative approach, incorporating direct observation of dance performances, in-depth interviews with community leaders and cultural practitioners, and analysis of relevant literature to gather comprehensive insights. Findings reveal that the Tuwu Dance is not merely an artistic expression; it embodies values of unity, courage, and spiritual reverence, deeply embedded in the everyday life of the Nias people. The dance involves vigorous and expressive movements, which showcase physical grace and strength, symbolizing resilience and communal solidarity. Furthermore, the Tuwu Dance serves as a vital medium for cultural transmission, ensuring that traditional values and identity are preserved and passed on to the younger generation. In conclusion, the Tuwu Dance plays a crucial role in maintaining cultural continuity and reinforcing social bonds, thus holding a revered place in the hearts of the Nias people.